Remove the Stumbling Blocks An Overview of the Concept of Oneness of God in Christianity and Islam as a Challenge and a Way for Interreligious Relation between the Two Religions - Jekonia Tarigan (P3TK, Sanata Dharma University, 2022)
Confession of faith is one of the most important part of religion. In Christianity’s confession of faith it is clear that there are mentioned what so called as Trinity in which Christians proclaim their belief to God the father, Jesus Christ and Holy Spirit. On the other hand, Islam have confession of faith in which they proclaim the oneness of God which is known as Tauhid. However, in the context of inter-religious relation between Islam and Christianity, their confession of faith often open a discussion even debate. Therefore, the Christian belief in a triune God and the deity of the Prophet Jesus are a serious “stumbling block” in dealing with Indonesian people in general and Islamic societies in particular. Concerning Islam, another question that immediately arises is, whether there is any interpretation which able to broke the ‘stumbling block’ or actually it is untranslatable of religion that should be accepted and honored? This kind of questions will be discussed in in this paper because the effort to remove these ‘stumbling block’ and built more harmonius inter-religious relation between Christian and Islam is both side duty.